5E-Metacognitive Lesson Plan in Education: Development and Validation for Higher Secondary School Students - Venkateswar Meher; Dr. Rajashree Baral (Universitas Pendidikan Ganesha, 2022)
Metacognition is an individual's ability to apply, and experience previously acquired to operate knowledge related to learning. This study aimed to develop 5E metacognitive RPP (Engage, Explore, Explain, Elaborate, Evaluate) in education and validate 5E metacognitive RPP with expert judgment. This type of research is development research. The research subject is a content validity expert. The test subjects were students in high school. The methods used in collecting data are interviews and questionnaires. The instrument used to collect data is a questionnaire. Questionnaires are used to collect data in the form of data provided by experts. The technique used in analyzing the data is descriptive qualitative, and quantitative analysis. Content Validity Ratio (CVR) is used as a quantitative measure to understand the content validity of the developed lesson plans. The results of data analysis are based on feedback and comments from experts and students. The final lesson plans are prepared. The overall content validity ratio of the developed learning plan is 0.73. So, the CVR value ranges from 0.6 to 0.8, so it can be seen that the lesson plans have good content validity. It was concluded that it could be used to teach high school students.